A Preliminary Study To Assess Consumer Conception On Online Vs Offline Purchase Of Medicines: Assess Consumer Conception On Online - Garg, Anshika (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: The use of the Internet for buying and selling of medicines has increased over several years.  Purchase of medicines from E-pharmacies has also grown exponentially with the increase in the usage of the internet for buying products. Online purchase of medicines comes with several advantages such as time-saving, variety of offers and quick home delivery but there are several disadvantages associated with it. Hence, to study the pros and cons of purchasing medicines online, this study was conducted. Methods: The main objective of this study is to assess the behaviour of consumers on online and offline purchase of medicines and what are the several factors that motivate them to purchase medicines online or vice-versa. For collecting responses, a questionnaire was prepared and distributed to the study participants through google forms. The questionnaire was divided into two sections including age and gender. Results: A total of 100 responses were obtained, out of which 50% of respondents opted for offline purchase of medicines from nearby pharmacies. In conclusion, it was observed that the majority of the population prefers the offline mode of purchase when it comes to the purchase of medicines and other healthcare products, though there are various major advancements in technology and variety of internet services and easy availability of e-medicines. Conclusion: It reflects a more health-conscious and traditional mindset and outlook of the people particularly while deciding about the mode of purchasing medicines- online or offline because people lack trust when it comes to online purchase of medicines.